Hong Kong Med J 2019
DOI: 10.12809/hkmj198086
|View full text |Cite
|
Sign up to set email alerts
|

Risk of post-contrast acute kidney injury in emergency department patients with sepsis

Abstract: Campaign, a care bundle of sepsis treatmentincluding fluid resuscitation, antimicrobial therapy, and source control-is recommended as life-saving treatment for patients with sepsis. 2 Computed tomography (CT) scanning is a popular method for ORIGINAL ARTICLE (20 vs 19 days, P=0.742). Conclusions: Intravenous contrast administration during CT scanning was not associated with prolonged length of hospital stay in patients with sepsis in an emergency setting. Moreover, the use of contrast-enhanced CT was not assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The majority of published studies showed that mortality was no different in patients who receive CM [8,15,18,19,[48][49][50][51][52][53][54] (Table 1). In-hospital dialysis following IV CM was extremely low in most studies except for reports that analyzed patients with sepsis [8,15,17-20, 48-51,53-55] (Table 1).…”
Section: Consequences Of Cin After Intravenous Administrationmentioning
confidence: 99%
“…The majority of published studies showed that mortality was no different in patients who receive CM [8,15,18,19,[48][49][50][51][52][53][54] (Table 1). In-hospital dialysis following IV CM was extremely low in most studies except for reports that analyzed patients with sepsis [8,15,17-20, 48-51,53-55] (Table 1).…”
Section: Consequences Of Cin After Intravenous Administrationmentioning
confidence: 99%
“…Of these, studies performed by Huang et al [ 28 ], Brito et al [ 21 ], and Dağar et al [ 12 ] found low incidences of temporary haemodialysis, with no patients requiring permanent haemodialysis. Hsu et al [ 25 ] also had no patients who required chronic dialysis, despite a relatively high incidence of emergent dialysis performed. McGillicuddy et al [ 13 ] had two CIN patients who required permanent dialysis after being discharged, but they only made up 0.3% of patients who underwent CECT in the ED.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, new initiation of dialysis and diagnosis of ESRD at 30 days for CECT patients in the ED were rare among patients with CKD receiving ICM [ 20 ]. Two studies also concluded that ICM administration during CECT in the ED does not increase the risk of emergent dialysis [ 25 , 27 ], diagnosis of CKD, and renal transplantation at 6 months [ 23 ]. While Cho et al [ 24 ] reported five ED patients with CIN after CECT receiving renal replacement therapy, it was initiated due to predisposing conditions such as multiorgan failure instead of ICM exposure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue of the Hong Kong Medical Journal, Hsu et al 5 conducted a study on patients with sepsis who received computed tomography scans with or without contrast media at a tertiary referral centre. The results showed no difference between the two groups in the incidence of AKI, emergent dialysis, mortality, and hospital stay.…”
mentioning
confidence: 99%